Succession Planning Practices among Nurse Managers at Korle Bu Teaching Hospital - Dapaa, A.B. (University of Ghana, 2019)
The pivotal role nurse managers’ play in hospitals cannot be overemphasized and as with most roles of similar nature, a great deal of knowledge and skill is needed for effective and efficient outcomes. Many nurse managers however, assume managerial positions without adequate formal preparation due to the absence of clear cut lines of succession and are therefore, faced with numerous challenges which affect patient outcomes and staff satisfaction. This study hence sought to explore the practice of succession planning among nurse managers at the Korle Bu Teaching Hospital, using the exploratory descriptive design. Twelve (12) nurse managers were purposely selected and interviewed using a semi-structured interview guide. The study was guided by the Leadership Succession Planning and Development framework. Data was analysed using thematic content analysis. The study found out that, succession planning increases nurses’ sense of career planning, helps retain intellectual capital and also helps in organizational vision attainment. The ranking system of progression is the main criteria nurse managers use in the appointment of potential successors. Challenges nurse managers encounter or perceive to encounter in the practice of succession planning include; frequent reshuffling, the tendency to generate conflict, a lack of incentives for nurse managers, and the ranking system of progression in nursing. Strategies that can be used to enhance the practice of succession planning include; promotion with preparation, provision of incentives for nurse managers, transparency in the succession planning process and talent identification. Potential nurse managers need to be identified at an early stage in their career and given the necessary preparation through a structured succession planning program to ensure efficiency and effectiveness when they assume managerial roles.
MPhil. Nursing
Keywords: Succession Planning; Korle Bu Teaching Hospital